Fiddly Fives: Management of Impacted Second Premolars. (2nd May 2021) - Hameed, Othman; Crawford, Elizabeth; Taylor, Nigel G
Abstract : Second premolars are the third most likely teeth to be affected by impaction after third molar and maxillary canine teeth. Although the presence of an impacted second premolar is relatively common, and is a situation that often presents to general dentists in practice, there is relatively little published regarding this topic. Knowledge of this condition is essential for all those involved with the management of these cases. This article explores the aetiology, assessment and treatment options available to manage this condition, using examples from cases treated within our department. CPD/Clinical Relevance: An understanding of the aetiology, assessment and various treatment options available to manage impacted second premolars will inform better treatment planning.